The Influence of Service Quality and Location on Student Decisions in Choosing the Faculty of Economics UNPRI - Dearma Br Simbolon; Hendry Hendry; Yeni Rafita Sihombing (Institute of Computer Science (IOCS), 2022)
The decision to choose is an alternative that is used to ensure the sustainability of a company. The factors that influence the decision to choose students are the quality of service and the location of the university to be chosen. The quality of service and location has an important role because the better the quality of service and location offered, the more students will be and the University will grow. Prima Indonesia University is one of the best private campuses in North Sumatra. The method used in this study is a quantitative method, with a population of 1,145 students. The sampling technique is random sampling using the Slovin formula in the sample calculation so that a sample of 92 students is obtained. The analysis used is multiple linear regression analysis, where previously the validity and reliability of the questionnaire to be used will be tested. Based on the results obtained, partially there is an influence of service quality on student decisions in choosing the Faculty of Economics UNPRI. Partially there is an influence of location on student decisions in choosing the Faculty of Economics UNPRI. UNPRI. The coefficient of determination test obtained is 42% where the variable of the decision to choose can be explained by the service quality and location variables and the remaining 58% is influenced by other variables not examined in this study. where previously will be tested the validity and reliability of the questionnaire that will be used. Based on the results obtained, partially there is an influence of service quality on student decisions in choosing the Faculty of Economics UNPRI. Partially there is an influence of location on student decisions in choosing the Faculty of Economics UNPRI. UNPRI. The coefficient of determination test obtained is 42% where the variable of the decision to choose can be explained by the service quality and location variables and the remaining 58% is influenced by other variables not examined in this study. where previously will be tested the validity and reliability of the questionnaire that will be used. Based on the results obtained, partially there is an influence of service quality on student decisions in choosing the Faculty of Economics UNPRI. Partially there is an influence of location on student decisions in choosing the Faculty of Economics UNPRI. UNPRI. The coefficient of determination test obtained is 42% where the variable of the decision to choose can be explained by the service quality and location variables and the remaining 58% is influenced by other variables not examined in this study. partially there is an influence of service quality on student decisions in choosing the Faculty of Economics UNPRI. Partially there is an influence of location on student decisions in choosing the Faculty of Economics UNPRI. Simultaneously there is an influence of service quality and location on student decisions in choosing the Faculty of Economics UNPRI. The coefficient of determination test obtained is 42% where the variable of the decision to choose can be explained by the service quality and location variables and the remaining 58% is influenced by other variables not examined in this study. partially there is an influence of service quality on student decisions in choosing the Faculty of Economics UNPRI. Partially there is an influence of location on student decisions in choosing the Faculty of Economics UNPRI. Simultaneously there is an influence of service quality and location on student decisions in choosing the Faculty of Economics UNPRI. The coefficient of determination test obtained is 42% where the variable of the decision to choose can be explained by the service quality and location variables and the remaining 58% is influenced by other variables not examined in this study. Simultaneously there is an influence of service quality and location on student decisions in choosing the Faculty of Economics, UNPRI. The coefficient of determination test obtained is 42% where the variable of the decision to choose can be explained by the service quality and location variables and the remaining 58% is influenced by other variables not examined in this study. Simultaneously there is an influence of service quality and location on student decisions in choosing the Faculty of Economics, UNPRI. The coefficient of determination test obtained is 42% where the variable of the decision to choose can be explained by the service quality and location variables and the remaining 58% is influenced by other variables not examined in this study.